(3gOGjI GdeSJQTOjf aj TQM ebOeI eYGde GdOjfs - (3GdCUagGfj, eMeO Jbj Hf eMeO GdQMjes ((3YHO GdcQje Hf eMehO GdLYaQjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhdg Gdabg ajceG fU Ydjg GdLhgQj hZjQg bGd Gddg fYGdi (B{ (3hdcf dG Jabghf JSHjMge (B} (3hNUg HYVge Hage ZQV GdeJcde ef cdGeg hBNQ Hage GdCTjGA GdObjbI haj eaQOGJ GdQGZH Cfg GdJhUd Edi Yde ZGFH (B...s
(3BNQgG (B:s
... (3aOaY Edjg GdeTJQj OQgeG ef ZjQ Cf jYjfg KefG eNUhU CMOgeG aYd jKHJ NjGQ GdJGNjQ dfSHI EjGg dZjQ GdebHhV dYOe JYjjf GdebHhV KefG dg Gh jHfi Ydi GddRhe CNPG HebJVi GdCUd dOhQGf GdKef HfjI hHjf GdebHhV hdfbWY GdcdGe aj GdeLdO GdGhd (B.s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3eWGdYI (B: (3eMeO HGbQ , (B1251 (3g`s
Keywords: (3CUhd Gdabgs